2011
DOI: 10.1007/s12185-011-0980-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of body mass index and other body composition parameters in early post-transplant complications in patients undergoing allogeneic stem cell transplantation with busulfan–cyclophosphamide conditioning

Abstract: Patients with impaired nutritional status may show increased risk of hematopoietic stem cell transplantation (HSCT)-related complications. This study was conducted to determine whether body mass index (BMI) and other body composition parameters, such as lean body mass index (LBMI) and body fat mass (BFM), are associated with early post-transplantation toxicity and mortality in allogeneic HSCT recipients. The records of 71 patients diagnosed with acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 13 publications
0
24
0
2
Order By: Relevance
“…When BMI is used to determine nutritional status, the results are contradictory. Le Blanc [30] found that pre-HSCT BMI was related to mortality; however, Hadjibabaie [4] and Sucak [5] did not observe the same. In the case of our study, the association between pretransplant nutritional status and mortality, established by BMI, was also not present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When BMI is used to determine nutritional status, the results are contradictory. Le Blanc [30] found that pre-HSCT BMI was related to mortality; however, Hadjibabaie [4] and Sucak [5] did not observe the same. In the case of our study, the association between pretransplant nutritional status and mortality, established by BMI, was also not present.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the most frequent are mucositis, constipation or diarrhea, immunological reactions, infectious complications and graft versus host disease [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…6,7,9,[14][15][16][17][18][19][20][21]25,27,28 The definition of significant aGVHD was as follows: grade III-IV in three studies, 7,9,18 and grade II-IV in the remaining studies.…”
Section: Definition Of Exposure Variablesmentioning
confidence: 99%
“…Most working groups have applied similar but slightly different body mass index (BMI) classifications according to the World Health Organization (WHO BMI) and the remainder employed very different cutoff values from the ratio of actual to ideal body weight (IBW). [1][2][3][4][5][6][7][8][9][10][11] Furthermore, the follow-up period for outcomes considered in one part of the studies covered at most the first post transplant year. 3,6,9,10 This therefore reveals the strengths of the present retrospective analysis, as we investigated for the first time the validity of three different weight classification tools using standard cutoffs as pretransplant prognostic factors, a long follow-up period of 7.2 years and a consistent chemotherapy dose adjustment in obese patients (Table 1) compared with most other studies with no adjustment or relevant information.…”
mentioning
confidence: 99%
“…2,6,10,11,14 However, other studies detected no association between obesity and OS. 1,2,[4][5][6][7]9 A recent metaanalysis by Nakao et al 13 focused on the overweight impact on HCT outcomes. By pooling pediatric and adult allo-HCT studies, overweight at transplantation was associated with worse OS and a higher aGvHD rate.…”
mentioning
confidence: 99%